KEABSAHAN HUKUM PENGIKATAN JAMINAN TANAH DALAM PRODUK RAHN TAJSILY DI PT PEGADAIAN – STUDI KASUS PEGADAIAN UNIT BUNGAH - Respati, Firmananta; Noor, Erma Zahro (HUKMY : Jurnal Hukum, 2024)
This study examines the implementation of the Rahn Tajsily Tanah product at the Pegadaian Unit Bungah, focusing on the process of securing land collateral, legal protection for both parties, and challenges faced during implementation. The findings reveal that the collateral binding process aligns with Islamic principles and regulations, particularly adhering to the DSN-MUI Fatwa No. 68/DSN-MUI/III/2008. However, the lengthy verification process poses a challenge. The legal protection provided ensures fairness and the absence of riba, securing the rights of both Pegadaian and the customers. Nonetheless, the challenges include prolonged verification times and a lack of customer understanding of the syariah contract. Suggestions include improving verification efficiency through collaboration with the National Land Agency (BPN), increasing public education on syariah principles, enhancing transparency, and exploring digital services to streamline processes. These improvements are expected to optimize the Rahn Tajsily Tanah product and its benefits for society.